Empty wind tunnel flow field computations. (1st March 2010) - Hantrais-Gervois, Jean-Luc; Cartieri, Aurelia; Mouton, Sylvain; Piat, Jean-Francois
In this paper we try to introduce CFD to an unconventional place: the wind tunnel. We aim at gaining physical information concerning the wind tunnel flow field. The aim of this paper is to assess the capability to model the flow physics of an empty wind tunnel with a closed test section. Detailed computations related to two major ONERA transonic wind tunnels are presented (S1MA and S2MA). The results of the different modelling of the wind tunnel flow field are presented and compared to experimental data.